Effect of Vyaghri Haritaki Lehya in Chronic Tonsillitis in Children of the Age Group 3-12 Years (International Journal of Ayurveda and Pharma Research, 2023)
Tonsillitis is the inflammation of the tonsils. The tonsils are two small glands on either side of the throat. The tonsils play a key role in helping the body to protect against infection. This is especially in young children, whose immune system is still developing. The tonsils act as a barrier, trapping an infection and stopping it spreading to other parts of the body. In Ayurveda tonsillitis is correlated with Tundikeri, the disease of Talu (palate) and Kantha (throat), both of which are the Avaranas (establishment) of Mukharoga (diseases of mouth). Although no specific formulation for Tundikeri is given and surgical treatment is described for the disease, many formulations for Mukharogas (mouth disorders) are effective in Tundikeri. Vyaghri haritaki lehya is described by Bhaishajya Ratnavali and Chakrvadatta. It is also included in Bhava Prakasha, Yoga Ratnakara, Gada Nigraha, Vanga Sena samhita and Bharat Bhaishajya Ratnakar. A case study of 20 children on chronic tonsillitis done using Ayurveda medicine to improve general health.. Internal administration of Vyaghri haritaki lehya, the dose was 5gm for children between 3 to 6 years and 10gm for children between 7 to 12 years with lukewarm water as adjuvant, for a period of 60 days given. Follow up done after a period of 30 days.